Meta Analisis Pengaruh Model Discovery Learning pada Mata Pelajaran Fisika terhadap Berpikir Kritis Siswa - Uci A.Nababan, Lidia; Azhari Zulmi, M; Jesica Sihombing, Mia; Putrini R Harahap, Saima (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2023)
Education in Indonesia is now demanded to be even better in terms of student learning outcomes. Therefore this article was created with the aim of providing references related to learning models which in practice have been proven to improve student learning outcomes in schools. On this occasion the researcher only chose one learning model, namely Discovery Learning. Researchers conducted research using the meta-analysis method, which is an effort to summarize various research results by studying 6 data documents related to the use of Discovery Learning models published in national journals. The Discovery Learning learning model refers to students who are active and creative, because the Discovery Learning learning model expects each student to be able to master the learning material taught by educators. Because the learning model of Discovery Learning places more emphasis on students' direct experience and prioritizes the student learning process compared to the learning outcomes of these students